1990
DOI: 10.1093/infdis/161.1.127
|View full text |Cite
|
Sign up to set email alerts
|

Culture-Negative Endocarditis Probably Due to Chlamydia pneumoniae

Abstract: A 59-year-old man had culture-negative endocarditis (clinical evidence compatible with endocarditis and histopathologic evidence of a recent episode of endocarditis) and serology compatible with a recent episode of Chlamydia pneumoniae infection. The conclusion was that this episode of culture-negative endocarditis was probably due to C. pneumoniae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(22 citation statements)
references
References 12 publications
1
20
0
1
Order By: Relevance
“…Declining C. pneumoniae IgM titers during the observation period suggested primary infection. Our findings were in accordance with those of Marrie et al (13). Their patient had also shown declining IgM titers, whereas the patients described by other investigators had no IgM response, suggesting reinfection (4,15,16).…”
Section: Case Reportsupporting
confidence: 93%
See 2 more Smart Citations
“…Declining C. pneumoniae IgM titers during the observation period suggested primary infection. Our findings were in accordance with those of Marrie et al (13). Their patient had also shown declining IgM titers, whereas the patients described by other investigators had no IgM response, suggesting reinfection (4,15,16).…”
Section: Case Reportsupporting
confidence: 93%
“…Its role in endocarditis remains little documented. Among the approximately 20 published reports of Chlamydia endocarditis, C. psittaci was considered the etiologic agent in 11 reports, C. trachomatis was considered the etiologic agent in 2 reports, and C. pneumoniae was considered the etiologic agent in the remaining ones (4,6,10,13,14). In most of the cases, diagnosis was established solely by serology.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in a recent review of 10 patients reported to have chlamydial endocarditis, 8 were finally diagnosed with Bartonella endocarditis after their sera were tested by antibody cross-absorption and Western immunobloting (176,225). Interestingly, epidemiologic data for three of these eight patients were comparable to those reported for Bartonella endocarditis patients, including homelessness and alcoholism (172,176). Therefore, by using serologic testing only, it is difficult to know how many patients really have chlamydial endocarditis.…”
Section: ͻ150 ϫ 10mentioning
confidence: 93%
“…The reservoir of B. henselae is the cat, which is chronically bacteremic, and humans are likely to be the reservoir of B. quintana. Review of the literature and personal unpublished observations found a total of 54 cases of Bartonella endocarditis, 8 of which were caused by B. henselae (10,63,112,126,225), 20 were caused by B. quintana (30,65,131,168,225,257,258), 1 was caused by B. elizabethae (51), one was caused by B. vinsonii (239), and 20 were not characterized at the species level since they were diagnosed by serologic testing alone (75,172,225; unpublished data). Bartonella infection was diagnosed in 3 of 86 patients with endocarditis in Marseilles (3.5%), 3 of 123 patients with endocarditis in Halifax (2.4%), and 4 of 90 patients in Lyons (4.4%) (225).…”
Section: Agents Of Blood Culture-negative Endocarditismentioning
confidence: 99%